Integrating the Values of the Quran in Education to Form a Generation of Character - Nurjannah, Siti; Rizkiyah, Maulidah; Sumedi (Sunan Kalijaga International Journal on Islamic Educational Research, 2024)
This study aims to elaborate ideas on character education in Islam, referring to the Quran and Sunnah as the main guidelines for Muslims. The study also examines how these concepts relate to the current era of globalization. The focus of this study is character issues, which are very important to study, especially because of the dynamics of life in the current era of globalization. The research method used is literature study, which involves the use of primary data sources from the Quran as well as various relevant scientific papers. The Quran offers character education concepts such as faith in Allah (monotheism), compassion (including filial piety to parents and children), responsibility, and peace-loving. The results of this study increase our understanding of the importance of character education in overcoming the challenges faced in the era of globalization. This research finds that applying Islamic character values as the main foundation for building a firm and characterful character is very important in facing the increasingly complex dynamics of globalization.